Protein Data Integration through Ontologies - Sidhu, Amandeep (Nature Publishing Group, 2009)
In this paper, we consider the challenges of information integration in proteomics from the prospective of researchers using information technology as an integral part of their discovery process. Specifically, data integration, metadata specification, data provenance and data quality are discussed here. Here we review existing protein data integration methods and propose the use of common vocabulary for protein data integration using ontologies.